2010
DOI: 10.1242/jcs.059139
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylinositol phosphorylceramide is a major sphingolipid component and is required for proper localization of plasma-membrane proteins inSchizosaccharomyces pombe

Abstract: SummaryIn Saccharomyces cerevisiae, three classes of sphingolipids contain myo-inositol -inositol phosphorylceramide (IPC), mannosylinositol phosphorylceramide (MIPC) and mannosyldiinositol phosphorylceramide [M(IP) 2 C]. No fission yeast equivalent of Ipt1p, the inositolphosphotransferase that synthesizes M(IP) 2 C from MIPC, has been found in the Schizosaccharomyces pombe genome. Analysis of the sphingolipid composition of wild-type cells confirmed that MIPC is the terminal and most abundant complex sphingol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 74 publications
0
70
0
Order By: Relevance
“…Another interesting module is related to redox balance, lipid and glycan metabolism. It includes three glutathione S -transferase genes (Gst2, Gst3 and SPCC1281.07C) (Kim et al 2004), one NAD + /NADH kinase (SPCC24B10.02C), four mannosyltransferase (Imt1, Imt2, Imt3 and Omh1) (Nakase et al 2010), and one acyl-CoA-sterol acyltransferase (Are1). We also observed several modules which are related to signalling transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting module is related to redox balance, lipid and glycan metabolism. It includes three glutathione S -transferase genes (Gst2, Gst3 and SPCC1281.07C) (Kim et al 2004), one NAD + /NADH kinase (SPCC24B10.02C), four mannosyltransferase (Imt1, Imt2, Imt3 and Omh1) (Nakase et al 2010), and one acyl-CoA-sterol acyltransferase (Are1). We also observed several modules which are related to signalling transduction.…”
Section: Resultsmentioning
confidence: 99%
“…cerevisiae VAM7 was amplified from genomic DNA by PCR and was introduced into pART1 harbouring the constitutively strong adh1 + promoter (McLeod et al, 1987), resulting in pART1-VAM7. pREP1-GFP-Fsv1, pREP41-GFPFsv1 and pAU-Gms1p-RFP were made as reported previously (Takegawa et al, 2003a;Nakase et al, 2010). To construct pART1-GFP-Vsl1 and pART1-GFP-Fsv1, gfp-vsl1 + and gfp-fsv1 + were amplified by PCR using pREP41-GFP-Vsl1 and pREP41-GFP-Vsl1, respectively, as templates and introduced into pART1.…”
Section: Methodsmentioning
confidence: 99%
“…4b). To further analyse the localization of Vsl1p, we co-expressed GFP-Vsl1p and RFP-fused Gms1p, which is a UDP-Gal transporter and is used as a Golgi marker protein (Tabuchi et al, 1997b;Nakase et al, 2010), and revealed that GFP-Vsl1p was not co-localized with Gms1p-RFP (Fig. 4c).…”
Section: Vsl1p Is Localized To the Vacuolar Membrane And Prevacuolar mentioning
confidence: 99%
“…We previously reported that no fission yeast genes equivalent to Ipt1p have been found in the Schizosaccharomyces (Schiz.) pombe genome (Nakase et al, 2010). Sacc.…”
Section: Introductionmentioning
confidence: 99%
“…Schiz. pombe cells deficient in MIPC have been found to exhibit pleiotropic phenotypes, including defects in cell morphology and endocytosis, and in localization of ergosterols and plasma membrane-associated transporters (Nakase et al, 2010).…”
Section: Introductionmentioning
confidence: 99%